Discharging process of a finned heat pipe–assisted thermal energy storage system with high temperature phase change material. (15th June 2016) - Tiari, Saeed; Qiu, Songgang; Mahdavi, Mahboobe
Highlights: The discharging process of a latent heat thermal energy storage system is studied. The thermal energy storage system is assisted by finned heat pipes. The influences of heat pipe spacing and fins geometrical features are studied. Smaller heat pipe spacing enhances the solidification rate. Better heat pipe and fin arrangements are determined. Abstract: This paper presents the results of a numerical study conducted to investigate the discharging process of a latent heat thermal energy storage system assisted by finned heat pipes. A two-dimensional finite volume based numerical model along with enthalpy-porosity technique is employed to simulate the phase change of storage media during the discharging mode. The thermal energy storage system in this study consists of a square container, finned heat pipes, and potassium nitrate (KNO3 ) as the phase change material. The charging process of the same thermal energy storage system was reported in an early paper by the authors. This paper reports the results of discharging process of the thermal energy storage system. The influences of heat pipe spacing, fin geometry and quantities as well as the effects of natural convection heat transfer on the thermal performance of the storage system were studied. The results indicate that the phase change material solidification process is hardly affected by the natural convection. Decreasing the heat pipe spacing results in faster discharging process and higher container base wall temperature. Increasing the fins length does not change the discharging time but yields higher base wall temperature. Using more fins also accelerates the discharging process and increases the container base wall temperature.